Ex Libris Dr. med. Emil I. Bologa - Brujan, J.; Bologa, Emil I. (1916- ). (1964)
Profilowy portret mężczyzny, napis: Ex Libris Dr. med. Emil I. Bologa. Nazwisko artysty i data w obrębie kompozycji.
Keywords: Ekslibrisy